Analisis Pengaruh Nilai Tukar Terhadap Ekspor Komoditas Unggulan Indonesia - Taufiq, M.; Natasah, Nur Aliyah (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
his study aims to determine the effect of exchange rates on Indonesian commodity exports. Where the exchange rate is a comparison of the value or price of the Rupiah against other currencies. The dependent variable is the export of Indonesia's leading commodities, including Crude Palm Oil (Y1), Rubber (Y2) and textile (Y3) with the independent variable, namely the rupiah exchange rate (X). The data used in this study are time series data from 2012-2017. The method used is simple linear regression analysis, and is processed using the SPSS 16.0 program. The results of this study indicate that the rupiah exchange rate has a positive and significant effect on rubber export commodities and does not have a positive effect on palm oil (CPO) and textile commodities.